HUBUNGAN PENGETAHUAN DAN PERILAKU IBU TENTANG KELUARGA SADAR GIZI (KADARZI) DENGAN STATUS GIZI ANAK BALITA DI POSYANDU TERATAI, DUSUN SANANSARI, SRIMARTANI, PIYUNGAN, BANTUL,D.I. YOGYAKARTA TAHUN 2018 - Maylan Emilyani Dias Simon; Sarni Anggoro (Jurnal Delima Harapan, 2020)
Background: Malnutrition is one of the causes of morbidity and mortality in children under five years of age. Toddlers need nutrients in large quantities because of the rapid growth process. In 2017 there are 14% of children under five experiencing underweight. The national prevalence of nutritional problems among children under five in 2017 in the stunting category was 29.6% and underweight was 17.8% (Riskesdas, 2018). The malnourished sufferers of Piyungan Community Health Center work area are 3.8% and in Srimartani village there are 11.39% malnourished children under five. In addition, in the Sanansari Hamlet Posyandu in September there were 5.4% of children under five with underweight and stunting conditions. Research Objective: To find out the relationship between Knowledge and Behavior of Mother About Nutrition Conscious Family with Nutritional Status of Toddlers in Teratai Posyandu in Sanansari Village, Srimartani Village, Piyungan District, Bantul, D. I. Yogyakarta in 2018. Research Method: This research is a descriptive analytic research with cross sectional approach. The samples in this study were all toddlers in the Teratai Posyandu, which numbered 74 toddlers. The sampling technique is done by the Total Sampling technique. The statistical test used is to use Chi Square (x2). Results: Knowledge about Nutrition Conscious Family was partially in the good category (63.5%), the mother's behavior about Nutrition Conscious Family was partly in good category (90.5%), then there was a relationship between mother's knowledge and behavior about Nutrition Conscious Family at the Teratai Posyandu, Sanansari Hamlet, Srimartani, Piyungan, Bantul is characterized by a significant value of 0.050 and 0.00, respectively (P <0.05). Conclusion: There is a significant relationship between mother's knowledge and behavior about Nutrition Conscious Family and the nutritional status of children under five in Teratai Posyandu, Sanansari Hamlet, Srimartani, Piyungan, Bantul, Year 2018.